SOSIALISASI DALAM UPAYA MENINGKATKAN PEMAHAMAN PENGELOLAAN KEUANGAN KOPERASI PADA PENGURUS KOPERASI MERAH PUTIH DI DESA NIPA - Aliah Pratiwi; Firdaus; ST. Asyitah; Aris Munandar; Nurul Huda; Nafisah Nurulrahmatiah (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2026)
The Community Service and Community Service Program (KKN) in Nipa Village aims to address local economic challenges by improving financial literacy and strengthening community-based economic institutions. Despite its significant potential in the agriculture, livestock, fisheries, and micro-enterprise sectors, Nipa Village faces challenges such as weak financial management and the suboptimal role of cooperatives, particularly with the upcoming operational activities of the Merah Putih Cooperative. This program focuses on the socialization of the Merah Putih Cooperative. Through interactive training and direct mentoring, cooperative socialization activities help build community awareness and interest in cooperatives as a means of shared economic development. The results show increased awareness, changes in financial behavior, and residents' interest in participating in the utilization of the Merah Putih Cooperative. This program lays the foundation for a more structured, independent, and sustainable village economy.